ANALYSIS OF REGIONAL NEEDS AND MINING POTENTIAL IN THE POLICY ON ESTABLISHING BUMDs TO INCREASE REGIONAL ORIGINAL INCOME - Serli Tangmallun; Suhardi M. Anwar; Hadi Pajarianto; Ilham Tahier, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
The establishment of Regionally-Owned Enterprises (BUMD) in East Luwu Regency is one of the efforts to increase Regional Original Income (PAD). This article analyzes regional needs and mining potential in the BUMD establishment policy. The research method used is a qualitative method with a SWOT analysis approach and policy research, which is interpreted as a process to support policy making or analyze issues to help policy makers solve problems, through data analysis, statistics, and case studies in East Luwu Regency. Data were obtained from various sources, including relevant laws and government regulations, as well as case studies in East Luwu Regency. The potential of natural resources in the region, especially in the mining sector, has not been optimally utilized in supporting the increase in PAD, so strategic efforts and efforts are needed to obtain sources of regional income, through the establishment of BUMD. This study aims to analyze regional needs and mining potential in the BUMD establishment policy in East Luwu Regency and its impact on increasing PAD. The results of the study indicate that the mining sector is one of the regional potentials that is worthy of being developed by BUMD to increase PAD. Regional potential in the mining sector has a significant effect on the BUMD establishment policy in East Luwu Regency. The BUMD establishment policy makes a positive contribution to increasing PAD and can be beneficial for meeting community needs.